Fourteen small molecule and biological agents for psoriatic arthritis: A network meta-analysis of randomized controlled trials. Issue 31 (31st July 2020) - Qiu, Mingliang; Xu, Zhongbo; Gao, Wenjuan; Xiong, Meizhen; Wen, Xianhua; Zhu, Weina; Zhou, Xu; Yu, Minfeng
Abstract: Background: The comparative efficacy and safety of small molecule and biological agents in the treatment of psoriatic arthritis (PsA) remain unknown. Objectives: To compare the efficacy and safety of 14 small molecule and biological agents by network meta-analysis (NMA). Methods: Relevant randomized controlled trials involving biological treatments for PsA were identified by searching PubMed, Cochrane Library, EMBASE, Web of Science, and Clinicaltrials.gov and by manual retrieval, up to June 2018. NMA was conducted with Stata 14.0 based on the frequentist method. Effect measures were odds ratios (ORs) with 95% confidence intervals (CIs). Intervention efficacy and safety were ranked according to the surface under the cumulative ranking curve (SUCRA). Results: A total of 30 studies involving 10, 191 adult subjects were included. According to NMA, ≥ 20% improvement in modifed American College of Rheumatology response criteria (ACR20) response, Psoriasis Area and Severity Index 75 (PASI75) response, and serious adverse events rate (SAEs) were observed. In direct comparisons, most of the biologics performed better than placebo in terms of ACR20 response rate and PASI75 response rate. Additionally, all medicines were comparable to placebo in terms of SAEs except secukinumab. In terms of mixed comparisons, with regard to the ACR20 response, etanercept (ETN) and infliximab (IFX) were more effective than golimumab (GOL), with ORs of 3.33 (95% CI: 1.17–9.48) and 1.24 (95% CI: 0.61–2.52), respectively. For PASI75 response, IFX was superior to certolizumab pegol (OR = 10.08, 95% CI: 1.54–75.48). In addition, these medicines were comparable to each other in terms of SAEs. ETN and IFX were shown to have the most favorable SUCRA for achieving improved ACR20 and PASI75 responses, respectively, while ABT-122 exhibited the best safety according to the SUCRA for SAEs. Considering both the efficacy (ACR20, PASI75) and safety (SAEs), GOL, ETN, and IFX are the top 3 treatments. Conclusions and Implications: Direct and indirect comparisons and integrated results suggested that the 3 anti- tumor necrosis factor -α biologics (GOL, ETN, and IFX) can be considered the best treatments for PsA after comprehensive consideration of efficacy and safety. Abstract : Supplemental Digital Content is available in the text